Relationships between anthropometric characteristics, block settings, and block clearance technique during sprint start - Cavedon, V.; Bezodis, N. E.; Sandri, M.; Pirlo, M.; Zancanaro, C.; Milanese, C. (Journal of Sports Sciences, 2022)
This study aimed to identify how body dimensions interact with anteroposterior block distances to influence lower limb joint angles in the "set" position, how these angles relate to block clearance kinetic and kinematic parameters, and how these biomechanical parameters influence sprint start performance in sprinters of both sexes and of different ability levels. Seventy-eight sprinters performed six maximal-effort 10 m sprints. Joint angles in the "set" position were quantified through 2D video analysis, and the forces generated during block exit were measured by dynamometric starting blocks. Lower limb length was associated with the front block-starting line distance ([FB/SL], partial correlation [rPC] = 0.48) and was a significant predictor of FB/SL (R2 = 0.39). The FB/SL was associated with front hip angle (rPC = 0.38), which was consequently associated with numerous kinetic variables during block clearance (rPC from -0.41 to -0.61). Coaches should be encouraged to explore the interactions between individual lower limb lengths and the FB/SL distance in both male and female sprinters to manipulate the front hip angle in the "set" position in an attempt to achieve more favourable block clearance kinetics.